PEMANFAATAN PERPUSTAKAAN SEKOLAH DALAM MENUMBUHKAN LITERASI MEMBACA SISWA - Astriani, Yuni Resti; Sukirman, Sukirman; Hidayati, Dian (STKIP Pesisir Selatan, 2025)
Creating a literate generation is difficult; it requires collaboration from all parties. Therefore, instilling the habit of reading is necessary to develop knowledge and understanding of technology and other sciences, all of which students can gain when reading books. One place that can cultivate students' reading interest is the library. This research aims to determine the utilization of the school library in fostering students' reading literacy. The research was conducted at the library of SMP Muhammadiyah 5 Kota Cimahi. This study employed a qualitative approach. Data were collected through interviews and observations. The informants were the school principal and subject teachers. The research results show that teachers actively participate in literacy activities by providing comfortable facilities to cultivate students' reading literacy. The school collaborates with external parties and the regional library to improve service quality. The management of the school library to foster students' reading literacy includes implementing various literacy programs, such as the Friday Numeracy Literacy Program, to encourage students' reading literacy. Policies and support are needed to manage resources efficiently, including inventory and budget allocation.